The Effect of Organizational Structure on Ethical Decision Making - Muhammad Syafri; Egidius Fkun (Sean Institute, 2024)
This study examines how organisational structure affects modern business ethics. Various literature sources are collected and analysed for the study. Hierarchy, specialisation, departmentalization, range of control, and formalisation affect ethical decision making, according to the findings. Uncertainty and disagreement can inhibit ethical decision-making, but a clear and well-organized structure can create an environment that encourages it. Culture and leadership also moderate the impact of organisational structure on ethical decision-making. Organisational ethical decision-making is linked to ethical beliefs and principles. Therefore, organisations must understand how their organisational structure affects ethical decision-making, create a culture of open communication, transparency, and ethical dialogue, and ensure that policies and procedures support ethical decision-making. This research illuminates how organisational structure affects employees' ethical behaviour and decision-making, which can help establish ethical and sustainable management practices.